Sustainable production systems programme: current activities and future opportunities - Li Pun, H.H. (International Livestock Research Institute, 1998)
The main objective of ILRI's Sustainable Production Systems Programme is to improve human welfare through the development of more productive and Sustainable crop-livestock sytems in developing countries. The programmes' focus is on market-oriented smallholder crop-livestock systems. In order to improve the productivity and sustainability of these systems, biological, environmental and socio-economic constraints have to be overcome. Therefore, opportunities for changing the systems in a sustainable manner have to be carefully identified and chosen. Currently the programme has activities under four themes, viz, systems analysis and impact assessment, livestock policy analysis, market-oriented smallholder dairy and, improving livestock productivity under disease risk, and in three ecoregions, viz, highlands-Ethiopia, subhumid-Nigeria, and semi-arid-Niger.